Scaling up Deliberation: Testing the Potential of Mini‐Publics to Enhance the Deliberative Capacity of Citizens. Issue 3 (14th August 2020) - Suiter, Jane; Muradova, Lala; Gastil, John; Farrell, David M.
Abstract: This paper tests the possibility of embedding the benefits of minipublic deliberation within a wider voting public. We test whether a statement such as those derived from a Citizens' Initiative Review (CIR) can influence voters who did not participate in the pre‐referendum minipublic deliberation. This experiment was implemented in advance of the 2018 Irish referendum on blasphemy, one of a series of social‐moral referendums following the recommendations of a deliberative assembly. This is the first application of a CIR‐style voting aid in a real world minipublic and referendum outside of the US and also the first application to what is principally a moral question. We found that survey respondents exposed to information about the minipublic and its findings significantly increased their policy knowledge. Further, exposing respondents to minipublic statements in favour and against the policy measure increased their empathy for the other side of the policy debate.